An Iron Impurity in Multiwalled Carbon Nanotube Complexes with Chitosan that Biomimics the Heme‐Peroxidase Function. Issue 50 (6th November 2013) - Gayathri, Prakasam; Kumar, Annamalai Senthil
Abstract A new biomimetic functional system having an impure multiwalled carbon nanotube (MWCNT‐Fe)–chitosan biopolymer (H2N–CHIT) chemically modified glassy carbon electrode (GCE/[MWCNT‐Fe:H2N‐CHIT]) has been developed and demonstrated efficient hydrogen peroxide electrocatalytic and electrochemical sensing applications in pH 7 phosphate buffer solution (PBS). The hybrid system showed a stable and well‐defined surface confined redox peak at an apparent electrode potential, E°′=−0.22 V versus Ag/AgCl with surface excess value 13.63 nmol cm−2. Physicochemical characterizations of the hybrid by using FESEM, TEM, Raman spectroscopy, FTIR, and various control electrochemical experiments revealed that the iron impurity in the MWCNT interacted with the amino functional group of the chitosan polymer and thereby formed an unique complex‐like structure ([MWCNT‐FeIII/II:NH2‐CHIT]), similar to heme peroxidase with a central FeIII/II‐redox‐active site. The biomimetic system followed Michaelis–Menten‐type reaction kinetics for the H2O2 reduction reaction with a KM value of 0.23 mM. At pH 7, amperometric i–t sensing and flow‐injection analysis of H2O2 on the biomimetic system showed calibration plots in windows 5–500 and 50–2500 μM, with detection‐limit values of 2.3 and 9.7 μM, respectively. Unlike most of the previously reported systems that undergo serious interferences in physiological pH, the biomimetic system displayed a remarkable tolerance to other co‐existing interferants (such as cysteine, ascorbic acid, uric acid, nitrate, and nitrite), at a H2O2 detection potential similar to the peroxidase enzyme. The ability of the biosensor system to perform routine analyses was demonstrated by the detection of H2O2 present in simulated milk and clinical and cosmetic samples with appreciable recovery values.